Золотые сказки народов мира: [сборник / редактор Н. В. Хроменко] - Хроменко Н. В. (БАО, 2006)
Экземпляры: аб. (2007) / Инвентарный номер: 50813 / Цена: / Сис.шифр: 82.3(0) / Авт.знак: З-81 / ГРНТИ: 17.71.91 / ББК: 82.3(0)